ABOUT LIMITS OF THE FORCE SHOULDER FROM THE GENERATOR TO ROLLING ELEMENT OF BEARING (American Journal of Technology and Applied Sciences, 2024)
The article presents calculations for determining the force arm from the generator to the rolling element in order to determine the value of the generator force from the magnitude of the arm on the desired rolling elements